A hybrid indoor localization algorithm based on RSSI and inertial navigation - Yaping ZHU; Weiwei XIA; Yueyue ZHANG; Feng YAN; Xuzhou ZUO; Lianfeng SHEN (Dianxin kexue)
To cater for the requirements of high-precision indoor localization algorithms,a hybrid indoor localization algorithm based on received signal strength identification (RSSI) and inertial navigation was proposed.This algorithm used fingerprint identification algorithm to localize the agents,based on the RSSI values of ZigBee nodes in wireless sensor network.The algorithm combined the inertial information provided by inertial measurement units (IMU),to correct the RSSI localization results.This algorithm used Kalman filter and adopted state equations to describe the dynamic change rules of agents’ positions,thus it achieved a hybrid localization algorithm which relied WSN localization first and IMU last.Simulations evaluate that the proposed algorithm can improve the localization performances of algorithms which adopt RSSI localization and inertial navigation individually,and can greatly improve localization accuracy.